Strategi Dakwah Lintas Budaya dalam Menghormati Keberagaman dan Membangun Komunikasi Efektif - Muhammad Khasanul Huda (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2024)
Cross-cultural da'wah is an important approach in spreading the message of Islamic da'wah among people with diverse cultural backgrounds. This research uses a literature study method to explore principles, strategies and impacts. The results demonstrate the principles of respect for differences, effective communication, and adaptation to local culture. The strategy involves an intercultural, collaborative approach and the use of technology. It aims to build effective communication among diverse communities, spread Islamic teachings, and influence positive change.